An analysis of the Fairtrade cane sugar small producer organizations network. (10th December 2019) - Ruggeri, Giordano; Corsi, Stefano
Abstract: Over the last decades global sugar production and consumption have grown and the forecasts predict further increases in the coming years. Today 80% of the sugar in the world is produced from sugar cane, while only 20% is produced from sugar beet. Sugar cane production is mainly limited to tropical or sub-tropical areas, which production has always been linked to incidents of child labor, exploitation of workers, precarious working conditions and health problems for farmers. This paper provides a representation of the global sugar market, presenting the main players and the most evident trends, focusing on the network of Fairtrade (FT) certified producer organizations. The analysis uses data on sugar cane producers available in the literature (USDA, OECD, FAO) and data collected by the Monitory, Evaluation and Learning (MEL) program, which were provided by Fairtrade International. The database was analyzed using descriptive statistics techniques and two-step cluster analysis. The results identified four cluster that highlights recurring patterns and similarities of different indicators between producers' organizations in terms of their geographical location, productivity, type of cultivation, size of the organization and involvement in FT.